Pulmonary infection caused by Schizophyllum commune: a case study - Xue, Chunxue; Shen, Jiangtao; Song, Jie; Yang, Jingjing; Zhang, Shuming; Wang, Jinxiang (Frontiers in Medicine, 2025)
Although pulmonary infections caused by Schizophyllum commune (S. commune) are still relatively rare in clinical practice, they are increasingly familiar and valued by clinicians. The clinical symptoms and imaging of pulmonary infection with S. commune are not typical, thus diagnosis needs to be confirmed by clinical etiology. S. commune is one of the main fungal species causing allergic bronchopulmonary mycosis. The overall prognosis of S. commune pulmonary infection is good. This paper describes a case of a woman with no underlying disease who had pulmonary infection with S. commune. This report aims to improve clinicians’ awareness of the disease.